2014
DOI: 10.1016/j.jep.2014.05.055
|View full text |Cite
|
Sign up to set email alerts
|

The use of plants in the traditional management of diabetes in Nigeria: Pharmacological and toxicological considerations

Abstract: This review, therefore, provides a useful resource to enable a thorough assessment of the profile of plants used in diabetes management so as to ensure a more rational use. By anticipating potential toxicities or possible herb-drug interactions, significant risks which would otherwise represent a burden on the country׳s healthcare system can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
218
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(224 citation statements)
references
References 623 publications
4
218
0
2
Order By: Relevance
“…The most active non-polar fractions of A. camperi offered bioactive benzoic acid derivatives including 2-hydroxy-benzoic acid ethyl ester (ethyl salicylate) and 2-hydroxy-benzoic acid phenyl methyl ester (benzyl salicylate). Benzoic acid and its derivatives were reported to have antioxidant and anti-diabetic properties [21]. A study undertaken clarified the carboxyl group as being essential to the salicylate structural requirements for hypoglycemic activity [22].…”
Section: Gc-ms Analysis Of Fractionsmentioning
confidence: 99%
“…The most active non-polar fractions of A. camperi offered bioactive benzoic acid derivatives including 2-hydroxy-benzoic acid ethyl ester (ethyl salicylate) and 2-hydroxy-benzoic acid phenyl methyl ester (benzyl salicylate). Benzoic acid and its derivatives were reported to have antioxidant and anti-diabetic properties [21]. A study undertaken clarified the carboxyl group as being essential to the salicylate structural requirements for hypoglycemic activity [22].…”
Section: Gc-ms Analysis Of Fractionsmentioning
confidence: 99%
“…Insulin resistance results in decreased glucose uptake in striated muscles in combination with reduced glycolysis and fatty acid oxidation in the liver, leading to a series of modifications in the insulin signaling pathway, which attenuates signal transduction [8][9]. The mechanisms leading to the development of T2D have not been fully elucidated to date, but it is known that there are risk factors for developing the disease such as advanced age, obesity, poor eating habits, and a sedentary lifestyle [10]. After a period of compensatory hyperinsulinemia due to insulin resistance, the β-cells gradually lose their ability to meet the demands for the hormone in the body, resulting in a progression to hyperglycemia, which is characteristic of T2D.…”
Section: Introductionmentioning
confidence: 99%
“…The leaf extract has also been shown to enhance hepatic glutathione restoration [23]. Ethnobotanical surveys indicated that stem bark, leaves, and root extracts of these medicinal plants have been used for the treatments of various diseases in Nigeria [16,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%